The Effect of Giving Sukkari Date Juice on Breast Milk Volume in Postterm Mothers, 2025 - Fetrisa, Wiwit; Siska, Delvitria; Rahmadheny, Suci (International Health Sciences Journal, 2025)
Concurring to World Health Organization (WHO) data in 2018, exclusive breastfeeding reached 38%. This is still below the WHO target of 50% Exclusive Breastfeeding achievement. Sukkari dates have rich nutritional content, including carbohydrates and energy, vitamin B6, folic acid, minerals (calcium, magnesium, potassium), fiber, antioxidants. These contents play a role in increasing the energy and nutrients needed by mothers during breastfeeding. The purpose of this study was to determine the effect of giving sukkari date juice (Phoenix Dactylifera L) on the volume of breast milk in postpartum mothers in the obstetric room of Arosuka Hospital in 2025. The research design used was pre-experimental with a one group pre-test and post-test design. The research sample involved 14 breastfeeding mothers. The research was conducted in March 2025 to April 2025. The average volume of breast milk before being given Sukkari date juice was 27.79 and the average volume of breast milk after being given Sukkari date juice was 59.86. The p value of the research data is 0.000 (<0.05). Based on statistical analysis, it was concluded that there was an effect of giving Sukkari date juice (Phoenix Dactylifera L) on the volume of breast milk in postpartum mothers in the obstetrics room of Arosuka Hospital in 2025. The implication of this study is that the breastfeeding mothers can be encouraged to consume Sukkari date juice as an alternative before using drugs and supplements to stimulate breast milk production.